Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1363461518818282
|View full text |Cite
|
Sign up to set email alerts
|

Enacting autism: Immigrant family negotiations with nosology in practice

Abstract: This article describes how autism spectrum disorder is experienced in the context of immigrant families and how the meaning of this condition, proposed by professionals in the host country, is negotiated between families and healthcare providers. The study sample consists of 44 parents of different nationalities and their 35 children with autism spectrum disorder (ASD) living in a socioeconomically deprived neighborhood of Montreal, Canada. Individual parent interviews were audiotaped and transcribed for subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The results showed that the ASD group was significantly more exposed to environmental stressors; remained at home for longer periods of time and received less assistance on household tasks. Social distancing and the reference to lack of social support are environmental stressors that were already a part of ASD families before the pandemic 19 . On the other hand, the economic impact, the social distancing, the deprivation of outdoor activities, the risk of getting infected with the virus and the excess of media coverage and information are just a few potential factors that have been generating or aggravating symptoms such as anxiety, stress, fear, anger, guild, anguish, insomnia, feelings of loneliness and/or being trapped and depression in society 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the ASD group was significantly more exposed to environmental stressors; remained at home for longer periods of time and received less assistance on household tasks. Social distancing and the reference to lack of social support are environmental stressors that were already a part of ASD families before the pandemic 19 . On the other hand, the economic impact, the social distancing, the deprivation of outdoor activities, the risk of getting infected with the virus and the excess of media coverage and information are just a few potential factors that have been generating or aggravating symptoms such as anxiety, stress, fear, anger, guild, anguish, insomnia, feelings of loneliness and/or being trapped and depression in society 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In December of 2019, cases of pneumonia associated with severe acute respiratory syndrome (SARS) were first reported in China, specifically at the Hubei province and Wuhan city. The Coronavirus Disease (COVID- 19) is caused by a new coronavirus, denominated SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) by the World Health Organization (WHO). Due to its high transmissibility, COVID-19 rapidly spread throughout Europe and to the rest of the world, causing the WHO to declare the outbreak a pandemic on March 11, 2020 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Implications of this comparison are discussed in subsequent sections. Twelve studies focused on specific cultural and ethnic groups [18, 20, 31-35, 37, 38, 44, 48, 51], while 13 studies examined the experiences of newcomers from a variety of ethnic and cultural groups [19,21,30,[41][42][43][44][45][46][47][48][49][50]. Additionally, eight studies included both Canadian-born and immigrant caregivers of autistic children as participants [17,34,36,[38][39][40][41]52].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Other methods used included field notes, focus groups, and critical personal narratives. Data were gathered in English in 18 studies [19, 21, 31-35, 39, 41-50], French in 10 studies [21, 30, 40-43, 45-47, 49], Spanish in five studies [21,42,43,47,49], Chinese dialect in three studies [20,50,51], Portuguese in two studies [42,43], Korean in two studies [32,33],…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation